A Primary Study: Investigation of the In vitro Salt Stress Effects on Development in Thymus Cilicicus Boiss. & Bal - Agar, Hacer; Galatali, Selin; Ozkaya, Damla Ekin; Kaya, Ergun (Global Journal Of Botanical Science, 2022)
Since plants are soil-dependent organisms, they are directly exposed to biotic and abiotic stress factors. Of these factors, salinity has a direct effect on the growth and development of plants, and salinity at increasing rates can be critical for the viability of plant species. The current study aimed to investigate the effects of increasing in vitro salinity on the growth of endemic Thymus cilicicus Boiss. & Bal.. In this context, it has been observed that increasing concentrations of salinity suppress growth, and this study is a preliminary study to investigate the effects of salinity stress at the molecular level in the future.